Yo Resisto, Tú Resistes, Todos Resistimos: Modes of Resistance Displayed by U.S.-Born Children of Deported Parents on the Mexico/U.S. Border - Sandra L. Candel (MDPI AG, 2019)
Over 600,000 U.S.-born children are living in Mexico after being forced to leave with their parents after a deportation. Although these children possess transnational funds of knowledge, these go unrecognized by their Mexican teachers, who mostly view transnational students from a deficit perspective. This qualitative study included three transnational students aged 12−17 attending schools in northern Mexico due to parental deportation and used interviews, testimonios and thematic analysis to document their educational experiences and to determine their coping mechanisms and modes of resistance. By doing so, this study intended to highlight the ways in which participants enacted agency. The research questions guiding this study were: How are the educational experiences of transnational youth shaped by parental deportation? What tools do they use to cope? and, how does transnational youth enact transformative and other types of resistance? Based on theories of resistance and the Coyolxayhqui Imperative theory, this research found that the major obstacle transnational students face is the difference in educational systems and teaching practices and lack of academic Spanish proficiency. Deportation posed the added burden of stigmatization and exclusion. Family support was the greatest coping mechanism identified by participants, followed by friendships formed in Mexico, especially with other transnational students, as well as being resilient and purposeful in their pursuit of an education. Participants in this study displayed self-defeating, transformative, and resilient resistance. All people and place names are pseudonyms.